Einige Grenzwertsätze für additive zahlentheoretische Funktionen - Uždavinys, R. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Уждавинис. Некоторые предельные теоремы для аддитивных арифметических функций R. Uždavinys. Kai kurios adityvinių aritmetinių funkcijų ribinės teoremos